Methods to address poultry robustness and welfare issues through breeding and associated ethical considerations - Muir, William M.; Cheng, Heng-Wei; Croney, Candace (Frontiers in Genetics, 2014)
As consumers and society in general become more aware of ethical and moral dilemmas associated with confined rearing systems, pressure is put on the animal and poultry industries to adopt alternative forms of housing. This presents challenges especially regarding managing competitive social interactions between animals. However, selective breeding programs are rapidly advancing, enhanced by both genomics and new quantitative genetic theory and offer potential solutions by improving adaptation of the bird to existing and proposed production environments. The outcomes of adaptation could lead to improvement of animal welfare by increasing fitness of the animal for the given environments, which might lead to increased contentment and decreased distress in those systems. Genomic selection, based on dense genetic markers, will allow for more rapid improvement of traits that are expensive or difficult to measure, or have a low heritability, such as pecking, cannibalism, robustness, mortality, leg score, bone strength, disease resistance, and thus has the potential to address many poultry welfare concerns. Recently selection programs to include social effects, known as associative or indirect genetic effects (IGE), have received much attention. Group, kin, multi-level and multi-trait selection have all been shown to be highly effective in reducing mortality while increasing productivity of poultry layers and reduce or eliminate the need for beak trimming. Also, multi-level selection was shown to increases robustness as indicated by l greater ability of birds to cope with stressors. Kin selection has been shown to be easy to implement and improve both productivity and animal well-being . Because social effects are improved with such programs, it might be possible to increase stocking density, increase light levels, and use larger groups in floor pens. However, such changes raise ethical concerns that may constrain making these choices.